1998
DOI: 10.1016/s0092-8674(00)81226-x
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled Activates JNK and Discriminates between JNK Pathways in Planar Polarity and wingless Signaling

Abstract: Frizzled family proteins have been described as receptors of Wnt signaling molecules. In Drosophila, the two known Frizzled proteins are associated with distinct developmental processes. Genesis of epithelial planar polarity requires Frizzled, whereas Dfz2 affects morphogenesis by wingless-mediated signaling. Dishevelled is required in both signaling pathways. Here, we use genetic and overexpression assays to show that Dishevelled activates JNK cascades. Rescue analysis reveals different protein domain require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
762
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 731 publications
(800 citation statements)
references
References 58 publications
34
762
1
3
Order By: Relevance
“…DIX (Disheveled/Axin) domain located at the N-terminus (Capelluto et al, 2002) is responsible for interaction with a scaffolding protein Axin and functions exclusively in canonical Wnt signaling (Axelrod et al, 1998;Boutros et al, 1998; A B Moriguchi et al, 1999;Penton et al, 2002;Rothbächer et al, 2000). PZD (PSD-95, DLG, ZO1) domain located in the center mediates protein-protein interactions (Cheyette et al, 2002;Wong et al, 2003) and is required for all branches of Wnt signaling (Axelrod et al, 1998;Boutros et al, 1998;Moriguchi et al, 1999;Penton et al, 2002;Rothbächer et al, 2000). Finally, the DEP (Disheveled, EGL-10, Pleckstrin) domian situated at the C-terminus is essential for PCP signaling (Heisenberg et al, 2000;Moriguchi et al, 1999;Tada and Smith, 2000;Wallingford et al, 2000).…”
Section: Wnt Signaling Pathwaysmentioning
confidence: 99%
“…DIX (Disheveled/Axin) domain located at the N-terminus (Capelluto et al, 2002) is responsible for interaction with a scaffolding protein Axin and functions exclusively in canonical Wnt signaling (Axelrod et al, 1998;Boutros et al, 1998; A B Moriguchi et al, 1999;Penton et al, 2002;Rothbächer et al, 2000). PZD (PSD-95, DLG, ZO1) domain located in the center mediates protein-protein interactions (Cheyette et al, 2002;Wong et al, 2003) and is required for all branches of Wnt signaling (Axelrod et al, 1998;Boutros et al, 1998;Moriguchi et al, 1999;Penton et al, 2002;Rothbächer et al, 2000). Finally, the DEP (Disheveled, EGL-10, Pleckstrin) domian situated at the C-terminus is essential for PCP signaling (Heisenberg et al, 2000;Moriguchi et al, 1999;Tada and Smith, 2000;Wallingford et al, 2000).…”
Section: Wnt Signaling Pathwaysmentioning
confidence: 99%
“…Alternatively, JNK signaling may not be required for photoreceptor di erentiation per se, but for a distinct developmental event such as rotation of the eye facets. Indeed, genetic epistasis has placed bsk, hep, rhoA and dishevelled (dsh) in a pathway downstream of the Frizzled (Fz) serpentine receptor in generating proper tissue polarity based on dominant suppression, by mutations in these genes, of Fz-or dsh-induced ommatidial rotation defects (Boutros et al, 1998;Strutt et al, 1997). The connection between dsh and bsk is further supported by experiments in tissue culture cells which revealed that transfected dsh is capable of stimulating JNK activity (Boutros et al, 1998).…”
Section: Jnk Signaling In Tissue Polaritymentioning
confidence: 99%
“…Indeed, genetic epistasis has placed bsk, hep, rhoA and dishevelled (dsh) in a pathway downstream of the Frizzled (Fz) serpentine receptor in generating proper tissue polarity based on dominant suppression, by mutations in these genes, of Fz-or dsh-induced ommatidial rotation defects (Boutros et al, 1998;Strutt et al, 1997). The connection between dsh and bsk is further supported by experiments in tissue culture cells which revealed that transfected dsh is capable of stimulating JNK activity (Boutros et al, 1998). It remains to be determined whether the linkage between Fz/dsh and the JNK signaling cassette has any implications for DC, though it seems unlikely since dsh mutations lead to segmentation defects during embryogenesis and do not cause dorsal holes.…”
Section: Jnk Signaling In Tissue Polaritymentioning
confidence: 99%
“…For example, Wnt-11 regulates CE movements by means of Frizzled (Fz) and Dishevelled (Dsh; Heisenberg et al, 2000;Tada and Smith, 2000), which resembles PCP signaling pathway in flies. Furthermore, the specific domains of Dsh (Wharton, 2003) required for PCP signaling in CE movements during vertebrate gastrulation (Djiane et al, 2000;Heisenberg et al, 2000;Medina et al, 2000;Tada and Smith, 2000;Wallingford et al, 2000) are identical to those required in Drosophila (Axelrod et al, 1998;Boutros et al, 1998;Boutros and Mlodzik, 1999). In addition, CE movements in both Xenopus and zebrafish are controlled by the core PCP genes, including RhoA/Rac1 (Habas et al, 2001(Habas et al, , 2003Tahinci and Symes, 2003), JNK (Yamanaka et al, 2002), Rho-associated kinase-2 (ROK2, Marlow et al, 2002), Strabismus (Stbm, Darken et al, 2002;Goto and Keller, 2002;Jessen et al, 2002;Park and Moon, 2002), and Prickle (Takeuchi et al, 2003;Veeman et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%